Preparation and characterization of a novel galactomannan based bioink for 3D bioprinting. Issue 1 (June 2021) - Wu, Huaying; He, Ning; Huang, Yuting; Zhou, Zheng; Han, Xiaoxiao; Liu, Hairong
Abstract: The limited types of bioink significantly inhibit 3D bioprinting applied to tissue engineering. In this study, galactomannan (GM) was modified by a two steps modification method, by which GM was oxidized and then methacrylated. FTIR results showed that the two steps modification of GM is successful, and the prepared compound was named as OxGM-MA that was used to test whether it can be applied as a 3D bioprinting bioink. Compared with GM, the solubility of OxGM-MA increased and 4% (w/v) OxGM-MA solution was applied to further tests. This GM based bioink, the 4% (w/v) OxGM-MA solution, displayed a low viscosity, which is 8.5 mPa and is able to solidified by blue light irradiation. Additionally, its light solidified hydrogel displayed a pore network structure with the compressive strength of 52.3±6.7 kPa, which is strong enough for tissue engineering operations. By carrying chondrocytes, the GM based bioink was printed into a hydrogel with designed shape, which was created with CAD software previously. Following bioprinting, chondrocytes within the printed hydrogel exhibited good viability during 3 days incubation with cell culture medium, indicating the good printability and biocompatibility of the novel GM based bioink. It suggested that the novel GM based bioink can be potentially applied to cartilage tissue engineering in the future.